2017
DOI: 10.1111/ijcs.12373
|View full text |Cite
|
Sign up to set email alerts
|

Jingle bells or ‘green’ bells? The impact of socially responsible consumption principles upon consumer behaviour at Christmas time

Abstract: Socially responsible consumption (SRC) behaviours have progressed over the last few years and appear to show signs of a lasting trend. Situations of atypical consumption such as Christmas time, however, raise an important and as of yet unexplored question: What are the influences of unusual situations upon the relationship between people's socially responsible profile and their socially responsible purchase intentions (SRPI)? The objective of this article is thus to use the theory of planned behaviour (Ajzen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…In contrast, our scales do not seek to explain millennials' motivation to engage in SRCB but to identify millennials' SR behaviors and classify them as social signaling and self‐signals. Noted in previous literature (Robinot et al, ), SR consumption is categorized across three domains: purchasing, nonpurchasing, and disposition. The dimensions of the self‐signaling for SR consumption scale (consumption reduction and environmental concern) and the social signaling for SR scale are consistent with past literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, our scales do not seek to explain millennials' motivation to engage in SRCB but to identify millennials' SR behaviors and classify them as social signaling and self‐signals. Noted in previous literature (Robinot et al, ), SR consumption is categorized across three domains: purchasing, nonpurchasing, and disposition. The dimensions of the self‐signaling for SR consumption scale (consumption reduction and environmental concern) and the social signaling for SR scale are consistent with past literature.…”
Section: Discussionmentioning
confidence: 99%
“…Noted in previous literature (Robinot et al, 2017), SR consumption is categorized across three domains: purchasing, nonpurchasing, and disposition. The dimensions of the self-signaling for SR consumption scale (consumption reduction and environmental concern) and the social signaling for SR scale are consistent with past literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The former study found that consumers perceive supporting local musicians, through means such aspurchasing music or attending concerts, as a form of socially responsible consumption, while the latter suggests consumers may avoid buying products from socially responsible organizations to manage the gift-receiver's impressions of the gift-giver. Robinot et al (2017) investigated the impact atmospherics have on the relationship between people's socially responsible consumer (SRC) profile and their socially responsible purchase intentions (SRPI) in unusual situations such as holidays. They provide evidence suggesting that situation-specific atmospherics (in this case, Christmas) dampen the SRC-SRPI relationship and decrease consumers' otherwise consistent behavior by changing their attitudes.…”
Section: Socially Responsible Consumptionmentioning
confidence: 99%